Achieving High‐Performance Oxygen Reduction Catalyst and Zn–Air Battery through a Synergistic Nitrogen Doping Strategy. Issue 11 (6th September 2022) - Zhu, Xiaoran; Zhang, Jianze; Wang, Yan; Yang, Mingsheng; Yu, Haiping; Li, Tengfei; Hu, Mingjun; Yang, Jun
Abstract : It remains a challenge to achieve high‐performance, low‐cost, and robustly durable Fe, N co‐doped carbon‐based oxygen reduction reaction (ORR) catalysts with abundantly accessible Fe–N X sites. Herein, a novel scheme is designed to enrich the pore structure, increase the specific surface area, and generate spatially isolated Fe–N X sites of the ORR catalyst, in which pyridine nitrogen‐rich lamellar metal–organic complex (Fe–tetrapyridophenazine) is employed as the precursor and 2D graphitic carbon nitride (g‐C3 N4 ) as additional nitrogen source for achieving synergistic nitrogen‐doping effect. The introduction of g‐C3 N4 not only ameliorates the nitrogen coordination environment of metal active centers of the composite, but also increases the specific surface area and improves the pore structure. The resultant Fe–NC&CN composite has abundant active sites as well as remarkable electrical conductivity and suitable pore size for electron transfer and reactant diffusion. As expected, the catalyst exhibits excellent ORR activity, driving the reaction with low overpotential ( E 1/2 = 0.879 V) and remaining stable over a long reaction time (93% for 60 000 s), better than commercial Pt/C (20%) in all aspects. The assembled Zn–air battery exhibits high open‐circuit voltage of 1.566 V and high specific capacity of 815 mAh gZn −1, as well as stable and persistent discharge performance. Abstract : Synergistic N‐doping effect of Fe–tetrapyridophenazine (tpphz) and g‐C3 N4 leads to a super oxygen reduction catalyst Fe–NC&CN ( E 1/2 = 0.879 V), better than commercial Pt/C in all aspects owing to the abundant FeN X active sites, large specific surface area, suitable pore structure, and good conductivity. The assembled Zn–air battery (ZAB) with Fe–NC&CN also has an ultrahigh open‐circuit voltage of 1.566 V.